The Real-World Clinical Outcomes of Heavily Pretreated HER2+ and HER2-Low Metastatic Breast Cancer Patients Treated with Trastuzumab Deruxtecan at a Single Centre - Anna-Maria Lazaratos; Matthew Dankner; Aalya Hamouda; Soumaya Labidi; Victor Cohen; Lawrence Panasci; Jennifer E. Friedmann; François Patenaude; Cristiano Ferrario; Mark Basik; April A. N. Rose; Parvaneh Fallah (Current Oncology)
Background: Trastuzumab deruxtecan (TDXd) is an antibody–drug conjugate that has demonstrated impressive activity in randomized controlled clinical trials in the context of patients with HER2-amplified and HER2-low metastatic breast cancer. We aimed to review the activity and adverse event profile of TDXd in heavily pretreated breast cancer patients in real practice. Methods: We describe a single-center retrospective case series of metastatic breast cancer patients who were treated with TDXd. The outcomes of interest were the overall response rate, overall survival, progression-free survival and grade 4–5 adverse events. Objective responses and PFS were assessed in accordance with RECIST 1.1 criteria. Results: We identified 38 patients treated with TDXd. Of these, 15 patients had classically defined HER2-positive (HER2+) breast cancer, 4 of whom had active central nervous system (CNS) metastases. A total of 23 patients had HER2-low breast cancer, 2 of whom had active CNS disease. Of the 33 patients evaluable for response, 21 (63%) patients had a response to treatment, including three (9%) complete responses. Outcomes were similar between patients with a HER2+ and HER2-low status, as well as in patients with or without CNS metastases. No patients experienced grade 4 or 5 toxicities, and four of thirty-eight patients (10.5%) experienced pneumonitis (two patients with grade 3 pneumonitis, one patient with grade 2 and one patient with grade 1), resulting in TDXd discontinuation for three patients (with steroid administration in two patients). Conclusions: TDXd demonstrates impressive activity with manageable adverse event profiles in this heavily pretreated population that includes patients with active CNS metastases.